PERSONALITY CLASSIFICATION OF TEXT THROUGH MACHINE LEARNING AND DEEP LEARNING: A REVIEW (2023) - perera, himaya; Costa, Lakshan (International Journal For Research In Advanced Computer Science And Engineering, 2023)
Personality classification from text is a very popular domain of research among the domain of natural language processing. Personality of an individual has been found to be a very important characteristic when analyzing an individual for a particular purpose. Especially in fields such as e-recruitment, personality is a determining factor of if an individual has a placement at a particular workplace. The author aims to explore various personality classifications such as ‘The Big Five’ and the “Myer Briggs Type Indicator’ and various approaches in which text classification when it comes to detecting personality. Both machine learning and deep learning approaches are examined, and their inner workings, benefits and limitations are detailed as well. We expect that this article will provide a thorough insight to personality classification of text by a numerous number of approaches.